Clara Barrus and John Burroughs papers - Barrus, Clara, 1864-1931.; Burroughs, John, 1837-1921.
Correspondence, writings, estate papers, printed matter, scrapbooks, photographs, and other papers pertaining to the works and travels of Barrus and Burroughs and to the administration of their estates. Subjects include conservation, family matters, John Burroughs Memorial Association, lectures, philosophy, poetry, politics, publishing, and travels including a trip to Hawaii. Correspondents include Frederick Samuel Dellenbaugh, Clyde Fisher, Clara Bryant Ford, Hamlin Garland, William Temple Hornaday, Adeline Barrus Johnson, Robert Underwood Johnson, William Sloan Kennedy, John Muir, Carl Sandburg, Ernest Thompson Seton, Ida M. Tarbell, George Augustus Warburton, Walt Whitman, and editors at Houghton Mifflin Company.
Library of Congress Prints and Photographs Division.
Clara Barrus: physician, editor, and author; and John Burroughs: author and naturalist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Dellenbaugh, Frederick Samuel, -- 1853-1935 -- Correspondence; Fisher, Clyde -- Correspondence; Ford, Clara Bryant, -- 1866-1950 -- Correspondence; Garland, Hamlin, -- 1860-1940 -- Correspondence; Hornaday, William T. -- 1854-1937 -- Correspondence; Johnson, Adeline Barrus -- Correspondence; Johnson, Robert Underwood, -- 1853-1937 -- Correspondence; Kennedy, William Sloane, -- 1850-1929 -- Correspondence; Muir, John, -- 1838-1914 -- Correspondence; Sandburg, Carl, -- 1878-1967 -- Correspondence; Seton, Ernest Thompson, -- 1860-1946 -- Correspondence; Tarbell, Ida M. -- 1857-1944 -- Correspondence; Warburton, George Augustus -- Correspondence; Whitman, Walt, -- 1819-1892 -- Correspondence; Houghton Mifflin Company -- Correspondence; John Burroughs Memorial Association; American poetry; Philosophy; Poetry; Politics, Practical; Publishers and publishing; Voyages and travels; Hawaii -- Description and travel; United States -- Politics and government; Authors; Editors; Naturalists; Physicians